2022
DOI: 10.21203/rs.3.rs-1204181/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nonlinear co-generation of graphene plasmons for optoelectronic logic gates

Abstract: Surface plasmons in graphene provide a compelling strategy for advanced photonic technologies thanks to their tight confinement, fast response and tunability. Recent advances in the field of all-optical generation of graphene’s plasmons in planar waveguides offer a promising method for high-speed signal processing in nanoscale integrated optoelectronic devices. Here, we use two counter propagating frequency combs with temporally synchronized pulses to demonstrate deterministic all-optical generation and electr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Another strategy for light–matter interaction enhancement is the integration of 2D materials into optical fibers. [ 3,132,236–238 ] Zuo et al., have successfully grown by chemical vapor deposition (CVD) method 1L MoS2$\mathrm{MoS}_2$ on the internal walls of a SiO2$\mathrm{SiO}_2$ hollow capillary optical fiber (as shown in Figure 10d) [ 236 ] (CVD growth of MoS2$\mathrm{MoS}_2$ and WS2$\mathrm{WS}_2$ monolayers on the core of an optical fiber has been independently performed by Ngo et al. [ 239 ] ).…”
Section: Light–matter Interaction Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…Another strategy for light–matter interaction enhancement is the integration of 2D materials into optical fibers. [ 3,132,236–238 ] Zuo et al., have successfully grown by chemical vapor deposition (CVD) method 1L MoS2$\mathrm{MoS}_2$ on the internal walls of a SiO2$\mathrm{SiO}_2$ hollow capillary optical fiber (as shown in Figure 10d) [ 236 ] (CVD growth of MoS2$\mathrm{MoS}_2$ and WS2$\mathrm{WS}_2$ monolayers on the core of an optical fiber has been independently performed by Ngo et al. [ 239 ] ).…”
Section: Light–matter Interaction Enhancementmentioning
confidence: 99%
“…[214] Another strategy for light-matter interaction enhancement is the integration of 2D materials into optical fibers. [3,132,[236][237][238] Zuo et al, have successfully grown by chemical vapor deposition (CVD) method 1L MoS 2 on the internal walls of a SiO 2 hollow capillary optical fiber (as shown in Figure 10d) [236] (CVD growth of MoS 2 and WS 2 monolayers on the core of an optical fiber has been independently performed by Ngo et al [239] ). By tuning the excitation photon energy below the optical bandgap of MoS 2 to ensure low propagation losses for both incident radiation and generated harmonic signals, the authors demonstrated >300-fold enhancement of SHG and THG for a fiber length of ≈ 25 cm in comparison to MoS 2 on a fused silica substrate.…”
Section: Fibers and Waveguidesmentioning
confidence: 99%
“…Based on innovative designs of 2D-material-integrated nanostructured photonic devices, it is possible to further minimize optoelectronic devices' footprints as well as improve the operating speeds. Furthermore, since plasmons could be excited at the mid-IR even near-IR spectral region in 2D materials (e.g., graphene) [225,226], it opens an avenue to develop atomic-layer thickness plasmonic integrated circuits with ultracompact footprints and flexible electric-gate tunability for optical interconnects and sensing.…”
Section: Summary and Prospectmentioning
confidence: 99%